Faktor yang Mempengaruhi Kemiskinan dilihat dari Proporsi Sumber Daya Manusia Provinsi Jawa Barat 2018-2021 - Jordan A, Kevinindo; Mardjono, Enny Susilowati (Universitas Dian Nuswantoro, 2023)
Poverty is now starting to increase in number, and whatever happens in this situation will have an impact on socialiand economic problems. Even in West Java Province, Indonesia's poverty rate is still relatively high. The purpose of this study was to determine the factors that influence poverty in terms ofithe proportion ofiHuman Resources (HR) in West Java Province 2018-2021 in West Java Province between 2018-2021 using population, human development index, and unemployment as independent variables. The method’used in this research is multiple linear regression method. This type of research is descriptive quantitative with secondary data obtained from the Central Bureau of Statistics of West Java Province. There were 108 samples consisting of 27 districts/cities with data collection for 4 years. The results ofithe study show that the three variables namely population, human development index, and unemployment have an impact and influence on poverty in west Java Province in 2018-2021